Comparison of the ProSeal laryngeal mask airway and endotracheal tube in septorhinoplasty surgery - Dilek Yeniay; Bahanur Çekiç (Cukurova Medical Journal, 2021)
Purpose: The aim of this study is to use ProSeal laryngeal mask airway (PLMA) and endotracheal tube (ETT) in elective septorhinoplasty operation and to compare the hemodynamic differences and postoperative complications during the application. Materials and Methods: In the prospective planned study, ASA I-II and 60 patients aged 18-35 were randomly allocated into two groups (n = 30, n = 30). After the standard anesthesia technique, Group E was placed ETT, Group P PLMA. Patients’ demographic characteristics, number of attempts for correct insertion, hemodynamic changes, postoperative nausea, vomiting, sore throat, hoarseness, dysphagia and surgical satisfaction evaluated. Results: Heart rate was higher in Group E than in Group P at the 1st min after anesthesia induction, at the 1st, 2nd, 3rd, 4th, 5th, and 10th min after airway insertion, and at the 3rd min after extubation. Difficulty in swallowing at postoperative was higher in Group E than in Group P. Insertion rates of the devices, were similar. Surgical satisfaction was higher in Group E than in Group P. Adequate tidal volume was provided in both groups during the operation. Conclusion: The use of PLMA in airway management in outpatient septorhinoplasty operations creates less hemodynamic response compared to the use of ETT, less airway complications are seen and thanks to its flexibility, it does not interfere with the surgical area. PLMA may be an alternative to ETT when the insertion of the airway devices is performed by experienced physicians.